Preparation and catalytic properties of composites with palladium nanoparticles and poly(methacrylic acid) microspheres. Issue 11 (25th January 2014) - Bi, Shiyin; Li, Kun; Chen, Xi; Fu, Weigui; Chen, Li; Sheng, Huiying; Yang, Qing
<x xml:space="preserve">Abstract</x> Palladium (Pd) nanoparticles with different sizes are in situ synthesized by reduction of PdCl2 with NaBH4 as reductant in the presence of poly(methacrylic acid) (PMAA)microspheres. The obtained PMAA/Pd composites are characterized by Fourier transform infrared spectra, X‐ray diffraction, and Transmission electron microscopy. The catalytic activity of the PMAA/Pd composites is investigated using a model reaction, that is, reduction of p‐nitrophenol to p‐aminophenol. The reaction shows first‐order kinetics, and the reaction rate increases with increasing reaction temperature, p‐nitrophenol concentration, and loadings of Pd nanoparticles on PMAA microspheres. The PMAA/Pd composites exhibit good stability, ascribing to the Pd nanoparticles stabilized by PMAA microspheres. POLYM. COMPOS., 35:2251–2260, 2014. © 2014 Society of Plastics Engineers